The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijms23020795
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characterization and Transcriptome Analysis of New Dwarf and Narrow-Leaf (dnl2) Mutant in Maize

Abstract: Lodging is the primary factor limiting high yield under a high plant density. However, an optimal plant height and leaf shape can effectively decrease the lodging risk. Here we studied an ethyl methanesulfonate (EMS)-induced dwarf and a narrow-leaf mutant, dnl2. Gene mapping indicated that the mutant was controlled by a gene located on chromosome nine. Phenotypic and cytological observations revealed that dnl2 showed inhibited cell growth, altered vascular bundle patterning, and disrupted secondary cell wall s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Our results indicated significant chlorophyll content and fluorescence variations across years, leaf positions, and interactions. Previous research has shown that environmental factors, leaf traits, and internal structures significantly affect plant photosynthetic activity, thereby emphasizing the importance of season, climate, and canopy structure on photosynthetic efficiency [ 38 , 39 , 40 , 41 ]. The weight for genetic components in sugarcane photosynthetic efficiency varied between 15.055% and 28.498%, indicating that genetic factors primarily control photosynthetic traits in sugarcane [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated significant chlorophyll content and fluorescence variations across years, leaf positions, and interactions. Previous research has shown that environmental factors, leaf traits, and internal structures significantly affect plant photosynthetic activity, thereby emphasizing the importance of season, climate, and canopy structure on photosynthetic efficiency [ 38 , 39 , 40 , 41 ]. The weight for genetic components in sugarcane photosynthetic efficiency varied between 15.055% and 28.498%, indicating that genetic factors primarily control photosynthetic traits in sugarcane [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…For TipTop and DeviationTip, two traits that were significantly and negatively correlated ( Figure 9 ), Dwf4 is a common candidate gene for both traits. Previous studies showed that Dwf4 encoding putative cytochrome P450 superfamily protein was associated with changes in leaf angle in cereal crop species, such as maize ( Mantilla-Perez and Salas Fernandez, 2017 ; Dzievit et al., 2019 ; Han et al., 2022 ). TipTop indicated whether the leaf tip is the highest point of the leaf midrib curve, and DeviationTip represents the ratio of drooping length to LeafLength, and the drooping length is the length from the highest point to the leaf tip along the leaf midrib, both of them could have an effect on the leaf angle.…”
Section: Discussionmentioning
confidence: 99%
“…The known dwarfing genes Rht-B1b and Rht-D1b in wheat were considered GA-insensitive dwarfing genes due to their reduced response to GA (Peng et al, 1999), whereas the plant height of wheat Rht12 dwarf lines increased by more than 50% in the GA 3 treatment (Chen et al, 2014) and the wheat dwarf mutant DD399 also had significantly longer seedling and coleoptile lengths in the GA treatment than the non-treated control (Wu et al, 2021). Some dwarf mutants in plants, like the dwarf and narrow-leaf mutant dnl2 in maize, are GA biosynthesis-deficient mutants, with significantly lower GA concentrations than the wild-type mutant (Han et al, 2022). Inhibition of UI parenchyma cell extension in barley SS1 was possibly related to insufficient amounts of endogenous bioactive gibberellins (Pu et al, 2021).…”
Section: Msnsd Was Gibberellin-deficient But Ga-sensitivementioning
confidence: 99%
“…In wheat, peduncle tissues of DD399 comprised shorter cells than the wild-type ND399, which may have reduced its plant height (Wu et al, 2021). Likewise, the length of parenchyma cells significantly decreased in the maize dwarf mutant dnl2 (Han et al, 2022). In barley, the significantly reduced length of the uppermost internode in the mutant Sheathed Spike 1 (SS1) was attributed mainly to suppressed cell elongation (Pu et al, 2021).…”
Section: Dwarf Phenotype Of Msnsd Caused By Inhibited Cell Elongation...mentioning
confidence: 99%